2022
DOI: 10.7759/cureus.27928
|View full text |Cite
|
Sign up to set email alerts
|

Acute Necrotizing Encephalitis as an Early Manifestation of COVID-19

Abstract: In addition to respiratory symptoms, SARS-CoV-2 infection has been linked to numerous neurologic sequelae including acute necrotizing encephalopathy. Here we present the case of a 33-year-old woman infected with SARS-CoV-2 who arrived at the hospital unresponsive. She was comatose with intact brainstem reflexes, and brain imaging was consistent with acute necrotizing encephalopathy affecting the bilateral thalami, medial temporal lobes, and pons. She was treated quickly with intravenous corticosteroids and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The global COVID-19 pandemic has resulted in millions of SARS-CoV-2 infections and unprecedented morbidity and mortality ( 6 ). Although the respiratory system complications of COVID-19 have been the most frequent and life-threatening, increasing reports indicative of neurological complications ( 7 ), including encephalopathy ( 8 ), ANE ( 3 ), brain microhemorrhages ( 9 ), and Guillain–Barré syndrome ( 10 ), have emerged.…”
Section: Discussionmentioning
confidence: 99%
“…The global COVID-19 pandemic has resulted in millions of SARS-CoV-2 infections and unprecedented morbidity and mortality ( 6 ). Although the respiratory system complications of COVID-19 have been the most frequent and life-threatening, increasing reports indicative of neurological complications ( 7 ), including encephalopathy ( 8 ), ANE ( 3 ), brain microhemorrhages ( 9 ), and Guillain–Barré syndrome ( 10 ), have emerged.…”
Section: Discussionmentioning
confidence: 99%
“…Therapy with methylprednisolone, 1g intravenously daily followed by prednisone taper, and antiseizure drugs has been recommended [ 1 , 6 ]. Immunotherapy and plasmapheresis have also been reported [ 7 - 9 ]. Because of the rare manifestation of this clinical entity, specific guidelines have not been established yet.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of confirmed limbic and autoimmune encephalitis, SARS-CoV-2 can be both a triggering and a concomitant factor, as has been reported with other viruses [103,104]. For necrotizing and hemorrhagic-necrotic encephalitis cases, the relationship has since become more dubious in the absence of histology, as most of these reports are based on neuroradiology and can be mimicked by the systemic and vascular effects of the virus [82,[97][98][99]. The relationships and capabilities of SARS-CoV-2 to lead to the development of true encephalitis are further disputed by most morphological studies, as despite histology the morphological changes may be highly similar to those of encephalitis, and while there are data on micro-and astroglyopathy, as well as cytotoxic T lymphocyte infiltration, immunologically only a few studies have isolated viral presence in the central nervous system [9,62,67,78,105,106].…”
Section: Encephalitis and Encephalopathymentioning
confidence: 98%
“…As already mentioned, a focal point of research is the direct neurotropic effect of SARS-CoV-2 and its potential to lead to encephalitis, as in some of its close relatives [29,35,36,[91][92][93]. In the initial phases of the pandemic, multiple studies reported encephalitis in COVID-19 patients ranging from panencephalitis to acute hemorrhagic, acute necrotizing, limbic, and autoimmune encephalitis [82,[91][92][93][94][95][96][97][98][99][100][101][102]. In the case of confirmed limbic and autoimmune encephalitis, SARS-CoV-2 can be both a triggering and a concomitant factor, as has been reported with other viruses [103,104].…”
Section: Encephalitis and Encephalopathymentioning
confidence: 99%